Sacral Hiatus Study in Dry Human Sacra - Mishra, M; Singh, AK; Satyavathi, P; Sah, N (Janaki Medical College Journal of Medical Science, 2014)
Background and objectives: The sacral hiatus is the site for caudal epidural anaesthesia during perineal surgery and also for a painless delivery. It is also used for three dimensional colour visualization of lumbosacral epidural space in orthopaedic practice for diagnosis and treatment. Work on the morphometrical study of the sacral hiatus is limited, especially in south indian population. So this study is carried to examine, measure and record the morphometry of sacral hiatus in order to study the anatomical variations which will be useful for caudal epidural anaesthesia. Material and Methods: The study was conducted in the Department of Anatomy, Prathima Institute of Medical Science, Naganur, Andhra Pradesh. 93 dry sacra with complete sacral hiatus were taken for the study. The shape of the sacral hiatus was noted by naked eye. Level of the apex and base of the sacral hiatus was noted with respect to the sacral vertebra. The length of sacral hiatus was measured from apex to the midpoint of base, the anteroposterior depth of sacral hiatus at the apex was measured with the help of vernier calipers. The transverse width of sacral hiatus at the base was measured between the inner aspects of inferior limit of the sacral cornu with the help of divider and then adjusted, and calculated with vernier caliper. Results: In 47 (50.53 %) sacra the shape was Inverted-U and in 25 (26.9 %) sacra Inverted-V. The irregular shaped of sacral hiatus was observed in 11 (11.8 %) cases. A “Dumbbell” shaped sacral hiatus was observed in 5 (5.4%) cases with a nodular bony growth projecting medially from both margins. The dorsal wall of sacral canal was entirely absence in 4 (4.3%) cases. Absence of sacral hiatus, a rare phenomenon, was observed in 1 (1%) specimens only. Conclusion: In the present study, elongated hiatus and narrowing of the sacral canal at apex of sacral hiatus was found in a significant percentage, which should be kept in mind while giving the caudal anaesthesia in Andhra Pradesh region. DOI: http://dx.doi.org/10.3126/jmcjms.v2i1.11391 Janaki Medical College Journal of Medical Sciences (2014) Vol. 2 (1): 17-22